2010
DOI: 10.1007/s00586-010-1338-5
|View full text |Cite|
|
Sign up to set email alerts
|

Degenerative spondylolisthesis does not influence surgical results of laminoplasty in elderly cervical spondylotic myelopathy patients

Abstract: The objective of the study was to investigate the comorbidity of degenerative spondylolisthesis (DS), in elderly cervical spondylotic myelopathy (CSM) patients in our hospital, and the correlation between surgical results and preoperative DS. There are few studies on the outcome of laminoplasty for CSM with DS. A total of 49 elderly patients ([65 years old) who eventually had surgical treatment for CSM were evaluated. A slippage displacement of more than 2.5 mm at least at one level was classified to have a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…Of 123 patients, 57 patients (46.3%) were found to be unstable using flexion-extension views in five studies [5,6,8,9,11]. In the other study, Dean et al [10] reported 17 unstable levels (23.6%) of the 72 levels in 58 patients with degenerative cervical spondylolisthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 123 patients, 57 patients (46.3%) were found to be unstable using flexion-extension views in five studies [5,6,8,9,11]. In the other study, Dean et al [10] reported 17 unstable levels (23.6%) of the 72 levels in 58 patients with degenerative cervical spondylolisthesis.…”
Section: Resultsmentioning
confidence: 99%
“…1) [5][6][7][8][9][10][11]. Degenerative cervical spondylolisthesis was most common in C3/4 and C4/5, occurring in 81 patients at C3/4 (46%) and 87 at C4/5 (49.4%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5, 7, and 8). Shigematsu et al 23 reported that 87% of cervical degenerative spondylolisthesis had stabilized after laminoplasty, and Kawasaki et al 14 reported that in 93% of cases, degenerative spondylolisthesis occurred at C3-4 or C4-5. Given our results, we believe that cervical laminoplasty preserves cervical ROM without harmful intervertebral instability and is a reasonable and beneficial procedure for the treatment of elderly patients with myelopathy who have degenerative spondylolisthesis of the middle cervical spine.…”
Section: Figmentioning
confidence: 99%